Search for dark matter in events with a leptoquark and missing transverse momentum in proton-proton collisions at 13 TeV - Sirunyan, A.M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier, 2019)
A search is presented for dark matter in proton-proton collisions at a center-of-mass energy of TeV using events with at least one high transverse momentum () muon, at least one high- jet, and large missing transverse momentum. The data were collected with the CMS detector at the CERN LHC in 2016 and 2017, and correspond to an integrated luminosity of 77.4 fb−1. In the examined scenario, a pair of scalar leptoquarks is assumed to be produced. One leptoquark decays to a muon and a jet while the other decays to dark matter and low- standard model particles. The signature for signal events would be significant missing transverse momentum from the dark matter in conjunction with a peak at the leptoquark mass in the invariant mass distribution of the highest muon and jet. The data are observed to be consistent with the background predicted by the standard model. For the first benchmark scenario considered, dark matter masses up to 500 GeV are excluded for leptoquark masses GeV, and up to 300 GeV for GeV. For the second benchmark scenario, dark matter masses up to 600 GeV are excluded for GeV.